2019
DOI: 10.1096/fj.201802160r
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages treated with antigen from the tapeworm Hymenolepis diminuta condition CD25 + T cells to suppress colitis

Abstract: Macrophages play central roles in immunity as early effectors and modulating adaptive immune reponses; we implicated macrophages in the anticolitic effect of infection with the tapeworm Hymenolepis diminuta. Here, gene arrays revealed that H. diminuta antigen (HdAg) evoked a program in murine macrophages distinct from that elicited by IL‐4. Further, HdAg suppressed LPS‐evoked release of TNF‐α and IL‐1β from macrophages via autocrine IL‐10 signaling. In assessing the ability of macrophages treated in vitro with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Intravenous injection was subjected via retro-orbitally from week four to week seven ( Figure 2 A). Intravenous injection was chosen to effectively deliver the macrophages to the target site [ 32 , 33 ]. The body weight of the mice was weighed and compared to the control group every week.…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous injection was subjected via retro-orbitally from week four to week seven ( Figure 2 A). Intravenous injection was chosen to effectively deliver the macrophages to the target site [ 32 , 33 ]. The body weight of the mice was weighed and compared to the control group every week.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that helminths protect from colitis through induction of alternatively activated macrophages (M2) ( 4 ). Macrophages treated with antigen from helminth can protect against colitis ( 9 , 29 , 30 ). A recent study ( 9 ) has found that adoptive transfer of T. spiralis excretory/secretory (ES) -treated macrophages inhibited dextran sulfate sodium (DSS) -induced UC.…”
Section: Discussionmentioning
confidence: 99%
“…While these parasites feed in the small bowel, the adult tapeworms actively release excretory-secretory products (ESP) into the mucosa to modify their environment and circumvent the immune response of the host [3]. Tapeworm ESP have been shown to suppress inflammation by inducing regulatory B cells [4], tolerogenic dendritic cells [5], and regulatory T cells [6] which produce suppressor cytokines that keep inflammatory T cells and their effector molecules under control. These immunoregulatory strategies protect gastrointestinal tapeworms (such as D. caninum ) from being ejected by the immune response but also provide protection to the host (only when present in moderate numbers) against gastrointestinal inflammatory diseases that result from a dysfunctional immune system.…”
Section: Introductionmentioning
confidence: 99%